FORECAST FOR SCIENTIFIC RESEARCH DEVELOPMENT IN PEDIATRY FOR 2006-2010 - V.Yu. Al'bitskiy; I.I. Balabolkin; A.A. Baranov; N.R. Belova; T.E. Borovik; I.K. Volkov; S.N. Zorkin; A.A. Efimova; V.R. Kuchma; L.S. Namazova; G.V. Rimarchuk; L.M. Roshal'; et al. ("Paediatrician" Publishers LLC, 2006)
This publication contains the predictions of the scientific studies in pediatric patients. The forecast is developed by leading pediatricians of the country. It was based on the analysis of pediatrics developement and pediatric practice in the Russian Federation in recent decades.